ARAH PERKEMBANGAN DEMOKRASI DI PERDESAAN PASCA ORDE BARU - Heru Cahyono (Masyarakat Indonesia, 2012)
This paperexaminesthe directionanddevelopment ofruraldemocratizationinthe postNew Order era. There are variations inthe dynamicsandqualityof democracyfromonevillagetoanothervillage. In addition, theprospect ofdemocratizationstronglyinfluencedby theexistence of thediversityof social institutionsthat existineveryvillageTherefore, itis impossible to apply uniform democracyinIndonesia. The dynamic ofvillagedemocracyafter the New Order era is still very dependent onthe leadershipofpoliticalelite. The head ofthe villagelargely determinesthe direction ofpolitical lifeinthe village. Village leaderis animportant instrumentin changing theconsciousnessofthe community toparticipateinthe planningprogram. This in turnwill affect theavailability ofaccessandopennessof publicfacilities. In addition to villageleaders, agentsofdemocracyoccupiesa strategicpositioninpressing fordemocratizationagendainthecommunity. The socialstructure ofanegalitariansociety willnotbe usefulifcommunitiesdonotactivelyplay theroleof agent of democracy. Indonesiasruraldemocracyis stillat thelevel ofnon-participation. Insomecases, manipulation andtherapy are often usedaspaternalisticmethods. It remains a challenge to involvewider community membersduring project implementation.Keywords: rural, democracy, participation, and control.